PENGARUH PUPUK MAJEMUK DALAM MERANGSANG PERTUMBUHAN TUNAS PADA STEK DAUN Sansevieria trifasciata - Dewi Rosanti; Dian Mutiara (Universitas PGRI Palembang, 2011)
ABSTRACTThe research was conducted at The Laboratory of MIPA Graduate SchoolPGRI University from January to June 2011. The objective of this research was recognize the effect of leaf part sources Sansevieria trifasciata. The research utilized the Completely Randomized Design with five level treatment and six replications. The treatment are level consentration of fertilizer complex are 0 g/1 water (K0), 0,25 g/l water (K1), 0,5 g/l water (K2), 0,75 g/l water (K3), 1,0 g/l water (K4). The result showed that level consentration fertilizer give good effect to time of steam growth and length of steam Sanseviera trifasciata.Key words : fertilizer complex, Sanseviera trifasciata